2017
DOI: 10.1371/journal.pone.0183050
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional response to the olive fruit fly (Bactrocera oleae) reveals extended differences between tolerant and susceptible olive (Olea europaea L.) varieties

Abstract: The olive fruit fly Bactrocera oleae (Diptera: Tephritidae) is the most devastating pest of cultivated olive (Olea europaea L.). Intraspecific variation in plant resistance to B. oleae has been described only at phenotypic level. In this work, we used a transcriptomic approach to study the molecular response to the olive fruit fly in two olive cultivars with contrasting level of susceptibility. Using next-generation pyrosequencing, we first generated a catalogue of more than 80,000 sequences expressed in drupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 65 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…The expression of four defense genes associated with different hormonal pathways involved in plant defense (jasmonic acid, salicylic acid, and ethylene) was investigated. The selected genes represent some of the major mediators of plant defense responses to biotic stresses and environmental threats [ 64 , 65 , 66 , 67 ], and included: (i) ET, which encodes for a transcription factor belonging to the family APETALA2/ERF involved in ethylene signaling and the response pathway, in particular in hormonal cross-talk [ 68 , 69 ]; (ii) LOX, encoding for an enzyme that catalyzes the early steps of jasmonic acid (JA) biosynthesis, and influence local and systemic responses against many biotic and abiotic stresses [ 70 ]; (iii) TD, encoding for an ubiquitous disulfide reductase, enzymes that regulate the redox status of target proteins and play an important role in reactive oxygen species (ROS) scavenging during stress responses [ 71 ]; and (iv) PR27, encoding for a PR-protein included in a group of plant proteins induced in response to fungal, bacterial, viral, and viroid infection, and to some chemicals [ 65 , 66 ]. Interestingly, the fungal metabolite HA caused the upregulation of all selected defense genes, while the strains GV41 and KV906 produced a differential modulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of four defense genes associated with different hormonal pathways involved in plant defense (jasmonic acid, salicylic acid, and ethylene) was investigated. The selected genes represent some of the major mediators of plant defense responses to biotic stresses and environmental threats [ 64 , 65 , 66 , 67 ], and included: (i) ET, which encodes for a transcription factor belonging to the family APETALA2/ERF involved in ethylene signaling and the response pathway, in particular in hormonal cross-talk [ 68 , 69 ]; (ii) LOX, encoding for an enzyme that catalyzes the early steps of jasmonic acid (JA) biosynthesis, and influence local and systemic responses against many biotic and abiotic stresses [ 70 ]; (iii) TD, encoding for an ubiquitous disulfide reductase, enzymes that regulate the redox status of target proteins and play an important role in reactive oxygen species (ROS) scavenging during stress responses [ 71 ]; and (iv) PR27, encoding for a PR-protein included in a group of plant proteins induced in response to fungal, bacterial, viral, and viroid infection, and to some chemicals [ 65 , 66 ]. Interestingly, the fungal metabolite HA caused the upregulation of all selected defense genes, while the strains GV41 and KV906 produced a differential modulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR was carried out in a final volume of 12.5 microl, containing the 6.5 µL of 2× QuantiFast SYBR Green PCR Master Mix (Qiagen), the primer pairs (300 nM) and the cDNA template. Amplifications were performed as reported [61]. Primers and their temperature of annealing are presented in Supplementary Table S1.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…The research efforts aimed to investigate the interaction between the olive and its key enemy are relatively few compared with the economic impact of B. oleae [17]. In this context, studies clarifying the attachment ability of B. oleae in relation to the different physico-chemical features of the EW in different O. europaea cultivars could contribute to deepen the knowledge about this important insect pest, thus helping to develop control methods alternative to the use of pesticide harmful for human health.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae feed upon the olive pulp, thus causing losses of up to 80% of the oil value [15]. Although B. oleae is a key pest in the olive crop, some O. europaea cultivars are less susceptible to B. oleae adult females [14][15][16][17]. Based upon the investigations on the susceptibility of different olive cultivars to B. oleae [18][19][20], it was concluded that female attraction toward the different olive cultivars is due to the interaction of several physical (e.g., fruit size, weight, volume, color) and chemical factors.…”
Section: Introductionmentioning
confidence: 99%